Efectos de la aplicación de difenoconazole y estrobirulinas, solos y en mezcla para el control de la Roya (phakopsora pachyrhizi) en el cultivo de soya. - Coello Baños, Alexis Fabián (2013)
The exploitation of soybean after rice and maize is one of the short-cycle crops of major importance in the Ecuadorian coast. In the province of Los Rios are planted during the dry period, more than 50,000 ha, yields ranging from 1000-1800 kg / ha, a variation that is due to the use of technology developed by the crop. The soybean rust is a disease caused by the fungus Phakopsora pachyrhizi ) , with large numbers of primary hosts including soybeans ( Glycine max ) , wild soybean (G. sojae ) , habilla ( Pachyrhizus erosus ) , beans or bean (Phaseolus vulgaris) . Severe infection of the pathogen reduction performance therefore affects the producer financially. The aim of this investigation was to assess the efficacy of fungicides and estrobirulina difenoconazole alone or in mixtures, on the incidence and severity of disease, as well as their effect on yield and agronomic crop.